2000
DOI: 10.1017/s0007114500001872
|View full text |Cite
|
Sign up to set email alerts
|

Effects of replacing meat with soyabean in the diet on sex hormone concentrations in healthy adult males

Abstract: A randomised crossover dietary intervention study was performed to evaluate the effects of replacing meat protein in the diet with a soyabean product, tofu, on blood concentrations of testosterone, dihydrotestosterone, androstanediol glucuronide, oestradiol, sex hormone-binding globulin (SHBG), and the free androgen index (total testosterone concentration/SHBG concentrationÂ100; FAI). Forty-two healthy adult males aged 35±62 years were studied. Diets were isoenergetic, with either 150 g lean meat or 290 g tofu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 52 publications
(53 reference statements)
1
39
0
Order By: Relevance
“…Studies focusing on hormonal levels also found no clear effects (or borderline significance) when consuming tofu (70 mg/day isoflavones), soymilk (48 mg/day isoflavones), or soy products (22 mg/day isoflavones; Habito et al, 2000;Nagata et al, 2000Nagata et al, , 2001. A recent meta-analysis, which included studies that evaluated testosterone levels as a bio-indicator of risks for prostate cancer, suggested out of 32 reports that soy foods or isoflavone intake do not alter free testosterone levels (Hamilton-Reeves et al, 2010).…”
Section: Soy Phytoestrogens and Male Reproductive Functionmentioning
confidence: 99%
“…Studies focusing on hormonal levels also found no clear effects (or borderline significance) when consuming tofu (70 mg/day isoflavones), soymilk (48 mg/day isoflavones), or soy products (22 mg/day isoflavones; Habito et al, 2000;Nagata et al, 2000Nagata et al, , 2001. A recent meta-analysis, which included studies that evaluated testosterone levels as a bio-indicator of risks for prostate cancer, suggested out of 32 reports that soy foods or isoflavone intake do not alter free testosterone levels (Hamilton-Reeves et al, 2010).…”
Section: Soy Phytoestrogens and Male Reproductive Functionmentioning
confidence: 99%
“…Nine studies were identified that examined the effects of isoflavone supplements or soy foods on 17b-E 2 and/or estrone levels in men (84)(85)(86)(87)(88)(89)(90)(91)(92). As shown in Table 1, three studies (85,86,92) included older (>40 years) and six (84,(87)(88)(89)(90)(91) included younger men.…”
Section: Soy Isoflavones and Estrogenmentioning
confidence: 99%
“…In healthy males, various soy formulations have been evaluated in several studies to determine its effectiveness in decreasing testosterone and ultimately its role in reducing the risk of prostate cancer (15)(16)(17)(18)(19)(20)(21)(22). Most of these studies did not document a significant reduction in circulating testosterone, with the exception of the study by Gardner-Thorpe (18), which used a high concentration of soy isoflavone, and the study by Dillingham (22), which showed a minor reduction of hormone levels.…”
Section: Discussionmentioning
confidence: 99%